Impact of patient-reported outcomes on symptom monitoring during treatment with checkpoint inhibitors: health-related quality of life among melanoma patients in a randomized controlled trial - Lærke K. Tolstrup; Helle Pappot; Lars Bastholt; Sören Möller; Karin B. Dieperink (SpringerOpen, 2022)
Abstract Introduction In a randomized controlled trial, we previously investigated if melanoma patients receiving checkpoint inhibitors had fewer severe immune-related adverse events (irAEs) when they reported symptoms using electronic patient-reported outcomes (ePRO) with triggered alerts as an add-on to standard care, compared to standard care alone. The aim of this study is to examine between-group differences in health-related quality of life (HRQoL) and associations between irAEs severity and HRQoL. Methods The study population of 138 patients completed the EuroQol EQ-5D-5L Index and FACT-M questionnaires at baseline and weeks 24 and 48. We analyzed HRQoL from all patients who completed at least one questionnaire. Missing FACT-M items were imputed following existing guidelines. Results There was no difference in HRQoL at baseline as measured EQ-5D-5L between the intervention and the control group. Between baseline and 48 weeks, mean EQ-5D-5L scores were unchanged among patients in the intervention group (p = 0.81) but decreased significantly among patients in the control group (p = 0.03). Consequently, patients in the intervention group had higher mean scores than those in the control group (p = 0.05) at 48 weeks. Mean FACT-M scores did not differ significantly between the two groups at any of the time points. There were observed no between-group differences in mean EQ-5D-5 and mean FACT-M scores between patients with severe irAEs and patients who had none. Conclusion Melanoma patients receiving CPIs who self-reported irAEs using ePRO with triggered alerts as a supplement to standard care maintained their HRQoL compared to patients who received standard care alone. Patients in the intervention group had a significantly better HRQoL measured by EQ-5D-5L than controls 48 weeks after baseline. The results suggest that including ePRO in standard care increases melanoma patients´ well-being. Further and larger studies are needed to confirm this finding and examine the impact of severe irAEs on cancer patients' HRQoL. Trial registration: Clinicaltrials.gov NCT03073031 Registered 8 March 2017, Retrospectively registered https://clinicaltrials.gov/ .